Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas, dan Leverage Terhadap Nilai Perusahaan - Rosiyana, Intan; Setiawati, Erma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effect of firm size, profitability, liquidity, and leverage on firm value in the property and real estate sector listed on the Indonesia Stock Exchange during 2019–2023. The research employed a quantitative approach using secondary data from audited financial statements. The sample was selected using purposive sampling from 80 companies based on consistency in annual report publication, and completeness of research variables, resulting in 207 observations. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, and F-tests. The findings indicate that firm size has a positive effect on firm value, leverage has a significant negative effect, while profitability and liquidity have no significant impact. This study provides valuable insights for investors and company management in evaluating factors affecting firm value in the property and real estate sector.